Climatic niche evolution in the viviparous Sceloporus torquatus group (Squamata: Phrynosomatidae) - Martínez-Méndez,Norberto; Mejía,Omar; Ortega,Jorge; Méndez-de la Cruz,Fausto (PeerJ, 2019)
The cold-climate hypothesis maintains that viviparity arose as a means to prevent increased egg mortality in nests owing to low temperatures, and this hypothesis represents the primary and most strongly supported explanation for the evolution of viviparity in reptiles. In this regard, certain authors have stated that viviparous species will exhibit speciation via climatic niche conservatism, with similar climatic niches being observed in allopatric sister species. However, this prediction remains to be tested with bioclimatic variables relevant to each viviparous group. In the present study, we examined climatic niche evolution in a group of North American viviparous lizards to determine whether their diversification is linked to phylogenetic niche conservatism (PNC). We evaluated the phylogenetic signal and trait evolution of individual bioclimatic variables and principal component (PC) scores of a PC analysis, along with reconstructions of ancestral climate tolerances. The results suggest that diversification of the Sceloporus torquatus group species is associated with both niche differentiation and PNC. Furthermore, we did not observe PNC across nearly all bioclimatic variables and in PC2 and PC3. However, in Precipitation Seasonality (Bio15), in Precipitation of Coldest Quarter (Bio19) and in PC1 (weakly associated with variability of temperature), we did observe PNC. Additionally, variation of the scores along the phylogeny and Pagel’s delta (δ) >1 of PC3 suggests a fast, recent evolution to dry conditions in the clade that sustains S. serrifer.
Keywords: Niche evolution; Phylogenetic niche conservatism; Sceloporus; Phylogenetic signal; Viviparity; Cold-climate hypothesis; North America; Phylogeny; Phyloclimatic analysis; Niche disparity through time